A comparative study of stool antigen Immunocard STAT HpSA test with biopsy in diagnosis of H Pylori Infection - Rastogi, Munish; Rastogi, Dolly; Singh, Shraddha; Tewari, Sunita; Agarwal, Asha; Midha, Tanu (Indian Journal of Community Health, 2015)
The present study was conducted on 78 cases in the Department of Medicine at G.S.V.M Medical College, Kanpur who reported with various gastrointestinal symptoms such as dyspepsia, heartburns, nausea, vomiting and loss of appetite. They all were advised for biopsy by the physician. Patients treated with antibiotics, bismuth or proton pump inhibitors within 4 weeks preceding the study were excluded. Invasive tests using mucosal biopsies including histology and rapid urease test (RUT) were used to establish the gold standard in order to evaluate the accuracy of Immunocard STAT HpSA. Sensitivity, Specificity, Positive Predictive Value and Negative Predictive Value of Immunocard STAT HpSA as compared to gold standard were 95.5%, 81.8%, 96.9% and 75.0% respectively. It is thus concluded that the Immunocard STAT HpSA test has a diagnostic value comparable to the gold standard in detecting H Pylori. The sensitivity and specificity of the test is fair enough to be used as a test for screening purpose and also for diagnosis and treatment of H.Pylori infection in clinical practice